2022
DOI: 10.1007/s42761-022-00142-5
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Architecture of Attachment: New Insights into the Role for Oxytocin Signaling

Abstract: Social attachments, the enduring bonds between individuals and groups, are essential to health and well-being. The appropriate formation and maintenance of social relationships depend upon a number of affective processes, including stress regulation, motivation, reward, as well as reciprocal interactions necessary for evaluating the affective state of others. A genetic, molecular, and neural circuit level understanding of social attachments therefore provides a powerful substrate for probing the affective proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 182 publications
0
7
0
Order By: Relevance
“…Alternatively, or in combination, such sex differences in the NAc may arise from Oxtrregulated inputs to this region that differ between males and females 3,4,[58][59][60][61][67][68][69] . Consistent with this model, circuits that differ between the sexes influence the function of less dimorphic brain regions to generate sex-typical neural activity and behavior across species [70][71][72] the NAc between males and females may reflect that Oxtr signaling and other neuromodulatory pathways facilitating pair bonding evolved in prairie voles to act on ancestral, sexually dimorphic neural circuits 13,73,74 . Such neuromodulation may thus influence these pathways in prairie voles and other monogamous species to generate more monomorphic and synchronized reciprocal patterns of behavior to promote long-term attachment between mates 20,75-83 .…”
Section: Discussionmentioning
confidence: 77%
“…Alternatively, or in combination, such sex differences in the NAc may arise from Oxtrregulated inputs to this region that differ between males and females 3,4,[58][59][60][61][67][68][69] . Consistent with this model, circuits that differ between the sexes influence the function of less dimorphic brain regions to generate sex-typical neural activity and behavior across species [70][71][72] the NAc between males and females may reflect that Oxtr signaling and other neuromodulatory pathways facilitating pair bonding evolved in prairie voles to act on ancestral, sexually dimorphic neural circuits 13,73,74 . Such neuromodulation may thus influence these pathways in prairie voles and other monogamous species to generate more monomorphic and synchronized reciprocal patterns of behavior to promote long-term attachment between mates 20,75-83 .…”
Section: Discussionmentioning
confidence: 77%
“…While nonapeptide systems were not the focus of the current study, an intriguing follow-up question is how much of the pair bond transcription and its maintenance is attributable to nonapeptide dynamics. Recent publication of pair bond formation in Oxtr null voles provides a unique opportunity to identify oxytocin-dependent and independent transcriptional changes that support pair bonds ( Berendzen and Manoli, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of adult female prairie voles that display maternal behaviors is variable (18%–50%), and is dependent on rearing social conditions 46,47 . In this species, genetic ablation of oxytocin receptor using the clustered regularly interspaced short palindromic repeats (CRISPR) technique yielded striking results: the oxytocin receptor null prairie voles with no binding activity with 125 I‐OVTA were intact for maternal and paternal behaviors and pair bonding 41,48 . Mutant mothers were also able to transfer some milk to suckling infants, resulting in the survival of approximately half the litter, although their mean body weight was significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 In this species, genetic ablation of oxytocin receptor using the clustered regularly interspaced short palindromic repeats (CRISPR) technique yielded striking results: the oxytocin receptor null prairie voles with no binding activity with 125 I-OVTA were intact for maternal and paternal behaviors and pair bonding. 41,48 Mutant mothers were also able to transfer some milk to suckling infants, resulting in the survival of approximately half the litter, although their mean body weight was significantly reduced. Oxytocin receptor KO prairie voles were also created independently and it was reported that they exhibited reduced preference for social novelty and learning of peer-helping behavior and increased repetitive behaviors.…”
Section: Discussionmentioning
confidence: 99%